National oncofertility registries around the globe: a pilot survey - Ozimek, Noelle; Salama, Mahmoud; Woodruff, Teresa K. (Frontiers in Endocrinology, 2023)
Purpose: Oncofertility is an emerging discipline which aims to preserve fertility of young cancer patients. As fertility preservation services have become increasingly available to cancer patients in many countries around the globe, it is crucial to establish a foundation of collaborative reporting to continuously monitor and assess oncofertility practices. This survey study investigates the current global landscape of official national oncofertility registries, a vital tool which allows for surveillance of the field. Methods: An online pilot survey was conducted to give the opportunity to report official national oncofertility registries available in 2022. Survey questions covered the availability of official national registries for oncofertility as well as the official national registries for cancer and assisted reproductive technologies. Participation in the survey was voluntary, anonymous and for free. Results: According to our online pilot survey, responses were collected from 20 countries including Argentina, Australia, Brazil, Canada, Chile, China, Egypt, Germany, Greece, India, Japan, Kenya, Philippines, Romania, South Africa, Thailand, Tunisia, UK, USA & Uruguay. Only 3 out of the 20 surveyed countries have well-established official national oncofertility registries; and include Australia, Germany & Japan. The Australian official national oncofertility registry is part of Australasian Oncofertility Registry that also includes New Zealand. The German official national oncofertility registry is part of FertiPROTEKT Network Registry for German speaking countries that also includes Austria & Switzerland. The Japanese official national oncofertility registry includes Japan only and called Japan Oncofertility Registry (JOFR). A supplementary internet search confirmed the aforementioned results. Therefore, the final list of countries around the globe that have official national oncofertility registries includes Australia, Austria, Germany, Japan, New Zealand, and Switzerland. Some other countries such as the USA and Denmark are on their way to establish official national registries for oncofertility care. Conclusions: Although oncofertility services are expanding globally, very few countries have well-established official national oncofertility registries. By reviewing such a global landscape, we highlight the urgent need for having a well-established official national oncofertility registry in each country to monitor oncofertility services in a way that best serves patients.